Carotid revascularization and medical management for asymptomatic carotid stenosis: Protocol of the CREST-2 clinical trials. Issue 7 (October 2017) - Howard, Virginia J; Meschia, James F; Lal, Brajesh K; Turan, Tanya N; Roubin, Gary S; Brown, Robert D; Voeks, Jenifer H; Barrett, Kevin M; Demaerschalk, Bart M; Huston, John; Lazar, Ronald M; Moore, Wesley S; et al.
Rationale: Trials conducted decades ago demonstrated that carotid endarterectomy by skilled surgeons reduced stroke risk in asymptomatic patients. Developments in carotid stenting and improvements in medical prevention of stroke caused by atherothrombotic disease challenge understanding of the benefits of revascularization. Aim: Carotid Revascularization and Medical Management for Asymptomatic Carotid Stenosis Trial (CREST-2) will test whether carotid endarterectomy or carotid stenting plus contemporary intensive medical therapy is superior to intensive medical therapy alone in the primary prevention of stroke in patients with high-grade asymptomatic carotid stenosis. Methods and design: CREST-2 is two multicenter randomized trials of revascularization plus intensive medical therapy versus intensive medical therapy alone. One trial randomizes patients to carotid endarterectomy plus intensive medical therapy versus intensive medical therapy alone; the other, to carotid stenting plus intensive medical therapy versus intensive medical therapy alone. The risk factor targets of centrally directed intensive medical therapy are LDL cholesterol <70 mg/dl and systolic blood pressure <140 mmHg. Study outcomes: The primary outcome is the composite of stroke and death within 44 days following randomization and stroke ipsilateral to the target vessel thereafter, up to four years. Change in cognition and differences in major and minor stroke are secondary outcomes. Sample size: Enrollment of 1240 patients in each trial provides 85% power to detect a treatment difference if the event rate in the intensive medical therapy alone arm is 4.8% higher or 2.8% lower than an anticipated 3.6% rate in the revascularization arm. Discussion: Management of asymptomatic carotid stenosis requires contemporary randomized trials to address whether carotid endarterectomy or carotid stenting plus intensive medical therapy is superior in preventing stroke beyond intensive medical therapy alone. Whether carotid endarterectomy or carotid stenting has favorable effects on cognition will also be tested. Trial registration: United States National Institutes of Health Clinicaltrials.gov NCT02089217